We Roma a critical reader in contemporary art - Baker, Daniel; Hlavajova, Maria (BAK critical reader series, 2013)
"We Roma: a critical reader in contemporary art inquires into the contemporary moment through the lens of Roma artistic and intellectual practices, gathering knowledge from the Roma way of life. As the so-called West's misconceptions of itself, inherited from the legacy of the modern, are being unmasked through unprecedented shifts in politics, society, aesthetics, and economics--what can we learn from the commonalities among political struggles of historically marginalized communities such as Roma and in what we know as majority society? With the emblematic claim in the artistic imaginary "we Roma", including in it wider society--how can we invoke the possibility of a different world and alternative futures? Artists, theorists, writers, and activists--both Roma and non-Roma--speculate on such questions and the possibility of art to imagine the world otherwise." -- Provided by publisher